Driving Business Performance through Lean and Cloud-Based Supply Chain Integration: Evidence from the Oil and Gas Sector - Sultan, Muhammad Habifian; Hasan, Djohan Gunawan; Annas, Mohammad (Multidiscience : Journal of Multidisciplinary Science, 2025)
This study examines the synergistic impact of Lean Supply Chain Management (LSCM) and Cloud-Based Supply Chain (CSSC) integration on business performance within Indonesia’s oil and gas sector. Amidst global supply chain disruptions and Indonesia’s transition toward sustainable energy, optimizing supply chain efficiency has become a strategic imperative. While prior research highlights the benefits of LSCM in developed markets, its interaction with digital technologies in emerging economies remains underexplored. Adopting a positivist approach, this study employs a quantitative methodology, collecting data from 217 professionals in Indonesia’s oil and gas industry through structured questionnaires. Using Partial Least Squares Structural Equation Modeling (PLS-SEM), the research evaluates the direct and mediated effects of Just-In-Time (JIT) and Total Quality Management (TQM) practices on business performance, with CSSC as a mediator. Results confirm that both JIT and TQM significantly enhance business performance, with CSSC playing a pivotal mediating role by improving supply chain visibility, agility, and operational efficiency. The findings underscore the importance of integrating lean practices with cloud-based digital solutions to drive resilience and competitive advantage in volatile markets. This study contributes actionable insights for practitioners seeking to align operational excellence with digital transformation, offering a model for sustainable supply chain management in resource-intensive industries.